The Minskyan system, Part II: Dynamics of the Minskyan analysis and the financial fragility hypothesis - Eric Temoigne (Levy Economics Institute of Bard College, 2006)
This is the second part of a three-part analysis of the Minskyan framework. It studies in detail the dynamics at the root of the endogenous financial weakening of capitalist economic systems. This part combines the properties presented in part I with other important concepts, such as the paradox of leverage and conventional expectations, to explain the Financial Instability Hypothesis. It is demonstrated that the signs of fragility are not always visible and that financial weakening can take many different (even though well-defined) routes. This is used to draw some conclusion about the appropriate way to test for this hypothesis and the limit of data.
Keywords: E5; 330; Post Keynesian economics; Minsky; financial fragility